Impedance spectroscopy analysis of poly(3-hexylthiophene):TIPS-pentacene blends in different ratios - Vieira, Douglas Henrique [UNESP]; Ozório, Maiza da Silva [UNESP]; Nogueira, Gabriel Leonardo [UNESP]; Alves, Neri [UNESP] (Elsevier, 2021)
The 6,13-bis(triisopropylsilylethynyl)pentacene (TIPS-pentacene) is a promisor p-type solution-processable molecular semiconductor whose electrical properties are highly dependent on its morphology. Unfortunately, there is a great difficulty in controlling the TIPS-pentacene crystallization because it is extremely affected by many factors, as the deposition method, the solvent type, and others. Here, we studied thin-films of TIPS-pentacene blending with poly(3-hexylthiophene-2,5-diyl) (P3HT:TP blend) in different ratios, aiming to improve TIPS-pentacene morphology. The surface of each film was very dependent on the deposition method and the blend morphology exhibited a high variation with the ratio. The different crystallinities achieved lead to dramatic changes in the charge carrier transport properties throughout the film. The impedance spectroscopy indicated that the small addition of P3HT in the TIPS-pentacene greatly improves its conductivity, however, the TIPS-pentacene forms crystallite agglomerates that did not percolate, prevailing the P3HT conductivities.
Keywords: Blends; Conductivity; Impedance spectroscopy; P3HT; TIPS-Pentacene